A very rare skeletal dysplasia: spondyloepimetaphyseal dysplasia, sponastrime type - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2021)
We report a case of sponastrime dysplasia (SEMDSP), which was diagnosed by characteristic clinical and radiographic findings. The proband was the first child of consanguineous parents (first cousins once removed). A brother was 3 years old and healthy. The mother previously had a 3-month spontaneous abortion. After an uneventful pregnancy, the proband was born at term by vacuum-assisted vaginal delivery. His birth weight was 2800 g. He remained in neonatal ICU for 15 days due to respiratory distress and had physiological jaundice. He was breastfed for about 23 months and then fed by a formula. At the age of 7 years, he was investigated in pediatrics due to short stature and eventually referred to the medical genetics department because of short stature and facial dysmorphic findings. At the age of nine, his height was 111 cm (-3.8 SDS), weight 27 kg (-0.4 SDS) and head circumference 52 cm (-0.7 SDS). On examination, he had a prominent forehead, depressed nasal root and tip, arched eyebrows, hypertelorism, epicanthus, midface hypoplasia, anteverted nares, long philtrum, high arched palate, thin upper vermillion, macroglossia, cubitus varus, brachydactyly, shorthands, short phalanx and nails, short feet, short halluces, pes planus and genu valgum (Fig. 1). At the age of eight, he attended the pedodontics clinic complaining of crowding in his teeth. He had malocclusion due to midface hypoplasia, a high arched palate and prognathism. He also had a short lingual frenulum. There were tooth marks on the tongue edges due to macroglossia (Fig. 1). At 12 years old, his height is 117 cm (-4.72 SDS) and weight 38 kg (-0.8 SDS). He did not have any learning disabilities. In his psychometric evaluation, his mental development was found to be compatible with his age.
Keywords: Depressed nasal root; Midface hypoplasia; Prognathism; Short dental roots; Short-limb dwarfism